2020
DOI: 10.1007/978-3-030-59126-7_160
|View full text |Cite
|
Sign up to set email alerts
|

The Prospects for Using Distributed Ledger Technology in the Russian Insurance Sector

Abstract: Insurance is an essential financial instrument of a risk management system that helps to reduce uncertainty about future financial performance and mitigate consequences of various undesired events. However, the low level of financial literacy in general, and the insurance culture in particular, severely limits insurance market development in Russia. The development of new insurance products that would be understandable and transparent to a consumer is the most relevant issue in this area. The development of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 1 publication
(1 reference statement)
0
1
0
1
Order By: Relevance
“…The prospects for the use of digital technologies in insurance and their impact on the development of the insurance market in Russia were also considered by the authors of this article earlier, the risks associated with this process were identified and analyzed [Larina, Moryzhenkova, Kukanova, 2020].…”
Section: Discussionmentioning
confidence: 99%
“…The prospects for the use of digital technologies in insurance and their impact on the development of the insurance market in Russia were also considered by the authors of this article earlier, the risks associated with this process were identified and analyzed [Larina, Moryzhenkova, Kukanova, 2020].…”
Section: Discussionmentioning
confidence: 99%
“…Влияние цифровых каналов на качество обслуживания, корпоративную репутацию и прибыльность возрастает по мере развития рынка. Авторами настоящей статьи также выделялись и анализировались риски в страховании и их влияние на развитие страхового рынка [7].…”
Section: обзор литературыunclassified